Elevated levels of circulating histones indicate disease activity in patients with hand, foot, and mouth disease (HFMD) - Li, Xiuhui; Li, Qin; Li, Junhong; Li, Ying; Chen, Yuping; Lv, Aiping; Zhang, Jian; Ding, Jianbo; Von Maltzan, Kristine; Wen, Tao (Scandinavian journal of infectious diseases, 2014)
Abstract Background: Hand, foot, and mouth disease (HFMD) is a common infectious disease in children, characterized by acute viral infection accompanying acute inflammatory responses. Circulating histones are leading mediators of the inflammatory processes. This study aimed to elucidate whether circulating histones play a contributory role during HFMD. Methods: We measured plasma levels of histones, myeloperoxidase (MPO), lactate dehydrogenase (LDH), and cytokines in HFMD patients (n = 126) and compared the results with those of a control group (n = 30). Results: Circulating histone levels were significantly increased in HFMD patients (3.794 ± 0.156 μg/ml) compared with healthy controls (0.238 ± 0.023 μg/ml, p < 0.0001). In addition, their levels were remarkably higher in severe HFMD (n = 38) than in mild HFMD patients (n = 88) (5.232 ± 0.246 vs 3.293 ± 0.161 μg/ml, p < 0.0001). As for other inflammatory markers, MPO, LDH, IL-1β, IL-6, IL-10, MIP-1, and TNF-ɑ were found to be significantly higher in HFMD patients than in healthy subjects. Of these, LDH, IL-6, and TNF-ɑ levels correlated with disease severity (all p < 0.05). In mild HFMD, circulating histones correlated positively with plasma IL-6 and IL-10, whereas in severe HFMD, histones were associated with elevated IL-6 and TNF-ɑ levels. Conclusions: These data demonstrate that circulating histones are excessively released in patients with HFMD, which may indicate disease severity and contribute to systemic inflammation by promoting cytokine production (e.g. IL-6). We suggest that in mild HFMD, circulating histones may originate largely from neutrophil activation, whereas in severe HFMD, dying tissue cells and neutrophil activation may be synergistically involved in the increased levels of histones.